Gas-condensate potential of the middle-Jurassic petroleum system in Abadan plain, Southwest Iran: Results of 2-D basin modeling. Issue 10 (19th May 2018) - Kobraei, Mehdi; Rabbani, Ahmadreza
ABSTRACT: The Jurassic petroleum system has been proven as prolific oil and gas prospects in the southwestern of Iran. During this study, 2-D regional modeling was done on two selected sections (north-south and east-west); furthermore, 1-D models were reconstructed on 7 deeply drilled wells in order to evaluate petroleum generation and source rock maturity histories in the Abadan Plain area in southwest Iran. The results revealed that the Middle Jurassic Sargelu Formation with average present-time TOC and HI values of 2.65wt% and 151 mgHC/gTOC, respectively, can be classified as good to excellent type II source rock. The initial TOC and HI values regarded for modeling are 5wt% and 620 mgHC/gTOC, respectively. The geochemical maturity parameters indicate a wet gas window for the Sargelu Formation. The modeling results show that the maximum temperature and vitrinite reflectance in the Sargelu Formation has reached 150 oC and 1.3%VRo. Generation of hydrocarbon in the Sargelu commenced during the Early Cretaceous, while the main expulsion happened in the Paleogene. 2-D models show that the Jurassic source rock has already reached a high transformation ratio within the studied area and, due to lack of intense tectonic activity, the maturity is the same throughout the studied area. Oil and gas migrated mostly vertically to the overlying traps which are existed in the Jurassic and Cretaceous succession. The results predict the existence of gas-condensate in the Jurassic petroleum system of the studied area.